Gender and obesity modify the impact of salt intake on blood pressure in children - Correia-Costa, L (2016)
BACKGROUND:Most modifiable risk factors for high blood pressure (BP), such as obesity and salt intake, are imprinted in childhood and persist into adulthood. The aim of our study was to evaluate the intake of salt in children and to assess its impact on BP taking into account gender and nutritional status. METHODS:A total of 298 children aged 8-9 years were evaluated in a cross-sectional study. Anthropometric measurements and 24-h ambulatory monitoring were performed, and salt intake was determined by 24-h urinary sodium excretion. RESULTS:The average estimated salt intake among the entire cohort of children enrolled in the study was 6.5 ± 2.2 g/day, and it was significantly higher in boys than in girls (6.8 ± 2.4 vs. 6.1 ± 1.9 g/day, respectively; p = 0.018) and in overweight/obese children than in normal weight children (6.8 ± 2.4 vs. 6.1 ± 2.0 g/day, respectively; p = 0.006). Salt intake exceeded the upper limit of the US Dietary Reference Intake in 72% of children. Daytime systolic BP increased by 1.00 mmHg (95% confidence interval 0.40-1.59) per gram of daily salt intake in overweight/obese boys, but not in normal weight boys or in girls. CONCLUSIONS:Our results demonstrate an extremely high salt intake among 8- to 9-year-old Portuguese children. Higher salt intake was associated with higher systolic BP in boys, specifically in those who were overweight/obese. Longitudinal studies are needed to further evaluate the causal relationship between obesity and high BP and the mechanism by which salt intake modulates this relationship. Nonetheless, based on our results, we urge that dietary salt reduction interventions, along with measures to fight the global epidemic of obesity, be implemented as early in life as possible.